0211 Human Factors For Consultant Anaesthetists. (1st November 2014) - Shah, Tanuja; Gillam, Stephanie; Hawkins, Wendy; Cocking, Caroline; Foda, Ehab
Abstract : Background: Since 2006 I have been teaching medical students, and increasingly we have emphasised the importance of human factors in medical emergencies. It occured to me that this was not recognised when I trained and was likely to be so for many of my colleagues. This prompted me to design a half day course to deliver to colleagues and specialty doctors in my department to raise awareness of, and stimulate discussion about, human factors. Description: I devised a session involving 3 anaesthetists (consultants or specialty doctors) and an ODP. It consisted of an initial basic presentation followed by 3 emergency type scenarios using a SIM man 3G (Laerdel) and Anmedic anaesthetic machine. After each simulation there was a discussion which was based around human factors. I was mindful of anxieities individuals may have 'exposing' themselves in this way and so deliberately kept it in homogenous peer groups (consultants or specialty doctors). Results: The first course was run in November 2012. Since then I have run a further 4 courses for consultants and ODPS and 2 for specialty doctors. A total of 16 consultants 4 specialty doctors and 7 ODPs have completed the course. Feedback completed at the end of the course has been universally excellent with 100% of participants agreeing or strongly agreeing with the statements like 'this session will enhance my critical illness management' and 'The focus on human factors is important to me'. Free text feedback has included 'I think all member of the Critical Care department should do a simulation session as part of revalidation – every year' Potential impact: Raised awareness of the role of human factors in critical incidents has potential to prevent or improve outcome. THis can only be positive in an arena where the impact of human error is only just being recognised and acknoweledged.